Polymers used in ocular dosage form and drug delivery systems - Wagh, Vijay D; Inamdar, Beena; Samanta, M K (Asian Journal of Pharmaceutics (AJP), 2014)
Topical application of drugs to the eye is most popular and well-accepted route of administration for the treatment of various eye disorders. A variety of ocular dosage form and drug delivery systems, including a controlled release of the drug, drug targeting, and penetration enhancement of the drug, have been investigated. Polymers have been widely used as the drug carrier for controlled-release systems. Polymers release the drug as they themselves degrade and are sometimes finally absorbed within the body. In this article, several ocular drug delivery systems have discussed using different kinds of polymers and their acceptance over conventional.